0168 Death Certification In A Simulated Environment: Assessment Of Effectiveness Of Pre-simulation Course And Identification Of Issues With Death Certification In Final Year Medical Students. (1st November 2014) - Medjoub, Karima; Crichton, fiona; Edgar, Simon
Abstract : Background: As a newly qualified doctor, one of the daunting tasks to be learned and performed is the ability to certify death in a hospital setting. Junior doctors are frequently unsure about the steps of the examination required and apprehensive when asked to complete a death certificate. Methodology: The University of Edinburgh currently offers a simulation exercise to all the final year medical students prior to graduation. An essential part of the exercise is to certify a death and complete a death certificate. The students are asked to watch a video explaining the process in detail prior to attending the course. We have included 290 students in this study divided in groups of ten. Our aim is to assess and analyse the appropriateness and the accuracy of the examination. Results: Medical students have generally expressed feelings of uncertainty and anxiety around the subject of death certification. Data from the completed certificates will be collected and analysed. Each group is debriefed by tutors experienced in simulation-based training. The students will later be asked to report their experience in death certification once they start work as junior doctors, and also comment on benefits of the course with reference to specific aspects of simulation. Potential impact: We hope that by demonstrating the challenges facing the final year medical students when certifying a death in simulation, that the students would be engaged in taking part in a more interactive teaching style including a video of how to confirm and certify death appropriately. It has become clear to us how daunting and terrifying the first death confirmation is to the students even in a safe simulated environment. Conclusions: Issues surrounding death certification are a major concern to the newly qualified doctor, simulation offers a safe environment to identify and solve those issues. Reference: Certification of Death (Scotland) Act 2011. www.scotland.gov.uk